2020
DOI: 10.3390/ijerph17072425
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Validation and Reference Norms for the European Spanish Developmental Coordination Disorder Questionnaire: DCDQ-ES

Abstract: The Developmental Coordination Disorder Questionnaire (DCDQ) is a widely used and well-validated tool that contributes to the diagnosis of Developmental Coordination Disorder (DCD). The aim of this study was to further analyze the psychometric properties of the European Spanish cross-culturally adapted version of the Developmental Coordination Disorder Questionnaire (DCDQ-ES) in a sample of Spanish children aged 6–11 years and to establish reference norms with respect to age groups. Parents of 540 typically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…The European Spanish version of the DCDQ [ 29 , 30 ] was used to identify children at risk of DCD. The DCDQ is a well validated and widely used instrument to operationalize criterion B of the DSM-5 diagnostic criteria of DCD [ 7 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The European Spanish version of the DCDQ [ 29 , 30 ] was used to identify children at risk of DCD. The DCDQ is a well validated and widely used instrument to operationalize criterion B of the DSM-5 diagnostic criteria of DCD [ 7 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Items scores are summed to provide total and subscale scores, where higher scores indicate better daily motor performance [ 31 ]. The DCDQ has demonstrated good cultural equivalence, internal consistency (Cronbach’s α = 0.907), construct validity and discriminant validity in Spanish children (sensitivity = 76.7%; specificity = 83.3%; Area Under the Curve = 0.872) [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that the prevalence of DCD in Spanish children is high, as 8–12% of schoolchildren show risk of DCD [ 11 , 12 , 13 ]. Until now, the DCDQ is the only cross-culturally adapted and valid questionnaire available to identify children with probable DCD in Spain [ 14 , 15 ], but a measure that assesses both participation and quality of motor performance in a broad range of meaningful, functional daily activities in Spain is lacking. Additionally, academic researchers and health practitioners could benefit from having an instrument that addresses both performance and participation to further promote performance through participation in children with motor coordination issues, as recommended by the International Classification of Functioning, Disability, and Health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive review on ADHD prevalence conducted by Polanczyk et al, it was reported that 9.5% of children had a lifetime diagnosis of ADHD worldwide during the past three decades [ 7 ], while this prevalence ranges between 4.1% and 8.8% among Spanish children and adolescents [ 8 , 9 , 10 ]. Reported estimates of the prevalence of DCD in schoolchildren usually range between 5 and 6% [ 11 , 12 , 13 ] but recent studies have found that up to 12.0% of Spanish children are at risk of DCD [ 14 , 15 ]. While the prevalence estimates of ASDs are significantly lower, with approximately 1–2% of children presenting with an ASD, the consequences of these disorders in everyday living are much more severe and restrictive, thus making ASDs some of the most studied neurodevelopmental conditions [ 9 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%